MANAJEMEN KESISWAAN DALAM PEMBENTUKAN KARAKTER SISWA DI SMA NEGERI 1 SIMPANG TIGA KABUPATEN PIDIE - Julina, Julina; Iskandar, Iskandar; Marsithah, Iis (Hijri, 2025)
This study discusses student management in character building at SMA Negeri 1 Simpang Tiga, Pidie Regency, considering the importance of character development in raising students' awareness of good character and how to integrate character values into daily school activities. The aim of this study is to analyze the planning of student management by the principal in character building, the implementation of student management by the principal, and the evaluation of student management by the principal in shaping students' character. This research employs a qualitative descriptive approach. Data were collected through observations, in-depth interviews with the principal, school supervisor, school committee, teachers, school operator, students' parents, and students, as well as through document analysis related to school policies and programs. The results of the study are as follows: (1) The principal has managed student affairs well at SMA Negeri 1 Simpang Tiga, but improvements are still needed in certain aspects, such as the development of character curriculum and extracurricular activities. (2) The school supervisor emphasized the importance of parental and community involvement in supporting students' character development. (3) The school committee stressed the importance of effective communication between the school and parents in monitoring students' character development. (4) Teachers at SMA Negeri 1 Simpang Tiga have made efforts to shape students' character, but improvements are needed in areas such as the development of effective teaching methods. (5) Parents highlighted the importance of the school's active role in character building. (6) Students at SMA Negeri 1 Simpang Tiga have a good awareness of positive character traits, but there is still a need to improve their sense of responsibility and discipline.